A Systematic Review and Meta-Analysis of Healing Outcomes in Pediatric Lateral Humerus Condyle Fractures Treated with K-Wire Pin Fixation - Tom Lieven Stefan Kurniawan; Benny; Heru Rahmadhany (Universitas Muhammadiyah Palu, 2025)
Sagittal balance refers to the equilibrium between external forces acting on the spine, particularly gravity, and the body's response to maintain an upright position with minimal muscular energy expenditure. Disruption of this balance can lead to sagittal imbalance, which is linked to poor clinical outcomes in conditions such as adult scoliosis and degenerative spondylolisthesis. The sedentary lifestyle, especially in office workers who spend significant time sitting, makes understanding spinal alignment changes in various positions crucial. This study aims to assess the differences in lumbopelvic sagittal balance in standing, upright sitting, and relaxed sitting positions in a healthy population. This analytical study used a case series approach with 25 healthy subjects aged 18-40. X-ray images were taken in three positions: standing, upright sitting, and relaxed sitting. Parameters including lumbar lordosis (LL), sacral slope (SS), pelvic tilt (PT), pelvic incidence (PI), and PI-LL mismatch were measured using RadiAnt DICOM Viewer. Data were analyzed using ANOVA to compare the sagittal balance parameters across different positions. differences were found in LL, SS, PT, and PI-LL mismatch between positions (p < 0.05). LL was highest in standing and lowest in relaxed sitting. PT increased significantly in relaxed sitting, while SS was highest in standing. PI did not show significant changes across positions. Lumbopelvic sagittal balance varies significantly between standing and sitting positions, highlighting the need to consider sitting postures in spinal assessments. These findings provide valuable insights for spine surgery planning and postural assessments.